Students phobias of mathematics teachers at fourth grade elementary schools - Kusuma Wardhani, Dhita; Darmawan Kusuma Wardana, Mahardika (Universitas Nusantara PGRI Kediri, 2023)
This research was conducted with the background of existing issues faced by students when the mathematics teacher was teaching. The objective of this study is to obtain data related to the causes of mathematics teacher phobia among 4th-grade students in elementary schools. This research method used descriptive qualitative with a case study design and data collection techniques in the form of interviews, observations, and questionnaires conducted on students in 4th-grade elementary schools. The results of the study show that the punishment given by the teacher can make students phobia of the teacher because each student has different conditions. The phobia of students towards math teachers may arise due to the implementation of progressive discipline by the teacher towards each student. Many teachers consider a progressive discipline attitude as one of the most effective ways of educating students to be more disciplined, but this attitude makes a student phobia towards him because his psychology is different from other students. As a result, phobia can be shown directly from students, for example, students are afraid when dealing with math teachers so they will stay away from them as much as possible.